Aktivitas Antibakteri Ekstrak Sargassum plagyophyllum terhadap Bakteri Listeria monocytogenes dan Pseudomonas aeruginosa: Antibacterial Activity of Sargassum plagyophyllum Extract against Listeria Monocytogenes and Pseudomonas aeruginosa - Santhy W Sidauruk; N Ira Sari; Andarini Diharmi; Ilman Arif (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
Listeria monocytogenes and Pseudomonas aeruginosa are pathogenic bacteria that must be inhibited and killed using antibacterial compounds. Sargassum sp. is one of the type of brown seaweed which has bioactive compounds as antibacterial. The research was aimed to determine the bioactive compounds and antibacterial activities of Sargassum plagyophyllum extract. This research consisted of maceration and characterization of S. plagyophyllum which included phytochemical screening and gram positive and negative antibacterial analysis at different concentrations of extract (2, 4, and 6% w/v). Methanol extract of S. plagyophyllum had a yield of 1.32±0.04% and contained bioactive compounds such as alkaloids, steroids, saponins, and phenolics. Based on antibacterial activity, S. plagyophyllum extract had the inhibition zone diameter both for gram positive bacteria (L. monocytogenes) and gram negative bacteria (P. aeruginosa), Nevertheless, the inhibition zone diameter of gram negative bacteria (6.67±0.58 mm) was greater than gram positive bacteria (4.67±0.58 mm) at the highest concentration of extract (6%).